The relationship between the supply of money and stock market prices 'Malaysian case' / Moho Arif Yusa - Yusa, Moho Arif (Faculty of Accountancy, 1992)
As far as the investing public is concerned a share price is normally determined by the supply and demand of shares in the stock market. A stock exchange does not fix the share prices. It merely provides a medium of stock market place for investors to buy and sell their shares. Several macroeconomic variable can affect the stock market prices. The importance of these variable has been increasingly recognised and viewed by the most of the stock analysts. They study the movement of the variables and hope can be able to treat them as indicators of trends that can provide useful information about future stock prices. Share prices depend on the supply and demand for a particular stock. The term supply and demand -means the availability of a seller and buyer of stock respectively due to several variables. One of those popular variables that has been analysed and discussed is the supply of money. Investors need, money to invest. Therefore the money supply could lead to the change of the stock prices. There are numbers of studies and discussions as to determine the nature of the relationship between money supply and stock prices. And it. is frequently argued that movements in the aggregate indexes of common stock prices can be predicted from prior changes in the money supply. The results presented by some analysts indicate that although the supply of money is statistically related to stock prices, the relationship is much weaker than that claimed in some earlier studies.